Airborne quantification of upper tropospheric NOx production from lightning in deep convective storms over the United States Great Plains. Issue 4 (27th February 2016) - Pollack, I. B.; Homeyer, C. R.; Ryerson, T. B.; Aikin, K. C.; Peischl, J.; Apel, E. C.; Campos, T.; Flocke, F.; Hornbrook, R. S.; Knapp, D. J.; Montzka, D. D.; Weinheimer, A. J.; et al.
Abstract: The reported range for global production of nitrogen oxides (NO x  = NO + NO2 ) by lightning remains large (e.g., 32 to 664 mol NO x flash −1 ), despite incorporating results from over 30 individual laboratory, theoretical, and field studies since the 1970s. Airborne and ground‐based observations from the Deep Convective Clouds and Chemistry experiment in May and June 2012 provide a new data set for calculating moles of NO x produced per lightning flash, P (NO x ), in thunderstorms over the United States Great Plains. This analysis utilizes a combination of in situ observations of storm inflow and outflow from three instrumented aircraft, three‐dimensional spatial information from ground‐based radars and satellite observations, and spatial and temporal information for intracloud and cloud‐to‐ground lightning flashes from ground‐based lightning mapping arrays. Evaluation of two analysis methods (e.g., a volume‐based approach and a flux‐based approach) for converting enhancements in lightning‐produced NO x from volume‐based mixing ratios to moles NO x flash −1 suggests that both methods equally approximate P (NO x ) for storms with elongated anvils, while the volume‐based approach better approximates P (NO x ) for storms with circular‐shaped anvils. Results from the more robust volume‐based approach for three storms sampled over Oklahoma and Colorado during DC3 suggest a range of 142 to 291 (average of 194) moles NO x flash −1 (or 117–332 mol NO x flash −1 including uncertainties). Although not vastly different from the previously reported range for storms occurring in the Great Plains (e.g., 21–465 mol NO x flash −1 ), results from this analysis of DC3 storms offer more constrained upper and lower limits for P (NO x ) in this geographical region. Key Points: Moles of NO x produced per lightning flash are reported for six thunderstorms Two calculation methods are evaluated and compared using a common data set Results are compared with those for other storms over the U.S. Great Plains